If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3X + -12Y = -1 Solving 3X + -12Y = -1 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '12Y' to each side of the equation. 3X + -12Y + 12Y = -1 + 12Y Combine like terms: -12Y + 12Y = 0 3X + 0 = -1 + 12Y 3X = -1 + 12Y Divide each side by '3'. X = -0.3333333333 + 4Y Simplifying X = -0.3333333333 + 4Y
| -5(y+7)=5 | | -10=-x+2-2x | | X+7=3x-21 | | 4+-2y=-11+3y | | 12x-3=32x+2 | | 5x-10x+2=-6 | | 2m+2(3m)=102 | | -x+5x+7=8x+36 | | x^2+18x=-401 | | f(x+6)=2x+3 | | (-3)-2-(-10)2= | | -136+9x=85-8x | | 7x-85=2x-5 | | 27=-10n+n | | -3x+(13+5x)=3 | | x^3+20x^2-132x=288 | | 7h-9g=-3 | | (x)x=2y-6 | | 8c+3=6c-12 | | 10k-4k= | | 3y=5-1x | | 3x-6=46 | | x+6=8+x | | 7x-1y=-37 | | a(2a+6)(a-5)=0 | | x*3=2y-78 | | 7r+14=12+5r | | -3y=-8+-4y | | 3x+9(10)=2700 | | 7x-33=180 | | -22-8a=-1+6(4-5a) | | X+(x+2)+(x+4)=27 |